Kinematic Analysis of the Musculoskeletal System Diabetic Type I - Atiyat, Khaled; "Abdul Fattah", Osama; Zureigat, Ayed Ali (European Scientific Journal, ESJ, 2018)
This study aimed to apply the principles of biomechanics science correctly, also to be is nested in the treatment of diabetics, and establish kinematic record for musculoskeletal diabetics. In order to improve the quality of life and care for diabetics. To achieve this, the researchers used the kinematic analysis of the musculoskeletal system for (8) mail patients with type1 diabetes, purposive selected and belonging to Jordanian team of Diabetes (age: 21±0.7years, height: 164± 4 cm, mas:58± 0.2 kg, the experience of the disease, 13.3±0.8 years). The study sample was filmed by using video camera (Sony HDR-CX220E) reached speed (50) frame/s. The study results showed that musculoskeletal system for Diabetic Type I differences in their shape of musculoskeletal the rest of the population, consequently people with Type 1 Diabetes have a swayback posture and a lower chest forward posture. and the average of sample study in the flexion spine(77)° and (15)°for extension spine. Where it formed 81% from natural flexion spine and 45% from natural extension spine. The researchers recommend: the necessity informed Diabetic Type I on kinematic analysis of the musculoskeletal system.